Symbolic Deductive Reasoning using Connectionist Models - Mihai Horia Zaharia; Florin Leon; Dan Galea (Computer Science Journal of Moldova, 2004)
In this paper, we try to combine the possibility of symbolic deductive reasoning with the learning capability of the connectionist models. We introduce several algorithms for learning relations between concepts and finding paths in a transitive manner between learned concepts. An application that implements the proposed model is described and a number of case studies are presented.